Diversity of Medicinal Plant and Potential as Antibacterial in Peret Hill Forest, Tiang Tarah Village, District of Bakam, West Bangka - Monica Kharisma Swandi; Neli Sulastri; Fitri Ulandari; Mega Febriyanti (UNIVERSITAS NEGERI PADANG, 2021)
Traditional medicine that has been done by the Tiang Tarah Village shaman, Bakam District, Bangka Regency uses plants as medicine to cure various diseases. However, so far some plants that are used as medicine can not be proven definitively effectiveness against a disease. Therefore, this research was conducted with the aim of knowing which plants are used as traditional medicine in Tiang Tarah Village, Bakam District, Bangka Regency, exploring the diversity of medicinal plants in the Bukit Peret Forest, and testing the antibacterial activity of medicinal plants against Escherichia coli and Staphylococcus aureus bacteria. The research was conducted with several stages, namely: (i) Interviewing informants who are experienced in the field of traditional medicine (shaman) using snowball sampling techniques, (ii) Exploration in the Peret Hill Forest for sampling using roaming method, (iii) Antibacterial activity test medicinal plants against E. coli and S. aureus by using agar diffusion method. The results of the study obtained 22 types of medicinal plants interviewed by 3 shamans Tiang Tarah Village. Of the 22 species, only 14 were found during exploration in the Peret Hill Forest. 10 of them have antibacterial activity against E. coli and 11 types against S.aureus.